Land use proportion and walking: Application of isometric substitution analysis. (May 2019) - Sugiyama, Takemi; Rachele, Jerome N.; Gunn, Lucy D.; Burton, Nicola W.; Brown, Wendy J.; Turrell, Gavin
Abstract: Entropy measures of land use mix are a commonly used component of walkability. However, they present methodological challenges, and studies on their associations with walking have produced mixed findings. This study examined associations of the proportion of discrete land uses with walking, using isometric substitution models that take the complementary nature of land use proportions into account. Analysis of data collected from middle-aged adults living in Brisbane, Australia (n = 10, 794) found that replacing residential or other land with commercial land was associated with higher levels of walking. The isometric substitution approach may explain the potential impact of land use changes on residents' walking. Highlights: Entropy measures of land use mix are commonly used as a component of walkability. The entropy measure was not consistently associated with walking. Isometric substitution models examined associations of the proportion of land use with walking. Replacing residential land with commercial land was associated with higher levels of walking. Replacing other land with commercial land was associated with higher levels of walking.